Distribution of Tuvaella Brachiopod Fauna and Its Tectonic Significance - 王成文 李宁 孙跃武 宗普 (Journal of earth science (Wuhan, China), 2011)
Tuvaella brachiopod fauna are distributed in an arc in three areas, including the Zeya-Hailar （海拉尔）-Shinejinst area, the Najramdal Uul-Kyzyl area, and the Barkol-Fuyun （富蕴） area. The Tuvaella fauna in the Zeya-Hailar-Shinejinst area are distributed in the northern margin of Jiamusi （佳木斯）-Mongolia block along the Mongolia-Okhotsk suture between the Siberia plate and the Jiamusi-Mongolia block but not appear in the corresponding Siberia plate. The Tuvaella fauna in the Najramdal Uul-Kyzyl area are distributed in the southwestern part of the Siberia plate as the accelerated fold belts during the Salairian-Caledonian periods, and those in the Barkol-Fuyun area are distributed in the northeastern margin of Kazakhstan plate. They are distributed along the Irtysb suture between the Siberia plate and the Kazakhstan plate. The Tuvaeila fauna became domestic fauna during the Wenlock and Pridoli （Middle-Late Silurian） and form a unique biogeographic province, i.e., the Mongolia-Okhotsk Province. This biogeographic province is sustained to the Mississippian （Carboniferous）, perhaps due to the semiclosed state of the Mongolia-Okhotsk Ocean. The northeastern margin （right now the southwestern margin） of Siberia plate, the northern margin of Jiamusi-Mongolia block, and the northeastern margin of Kazakhstan plate might be conjuncted in an arc region from Wenlock to Mississippian, along the southern margin of the Irtysh-Mid Mongolia-Okhotsk Ocean. This is coincident with the fact that the Siberia plate rotated 180° clockwise since the Mesozoic and located in the middle-high latitude during Devonian, and the coral reef limestone is widely developed in the Jiamusi- Mongolia block during the Early and Middle Devonian, which suggests that the block was positioning in middle-lower latitude at that time and that the Kazakhstan plate was also located in low latitude then.